Molecular detection of microorganism in prostate cancer and urinary tract infection in Iraq - Iman Hamid Al-Araji; Ali Abdul Kadhim Al-Ghanimi; Wafaa Sadiq Al-Wazni (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infections associated with mortality in cancer patients are mainly attributed to bacteria, and since infections in cancer patients may disrupt the treatment pattern and increase or decrease the survival rate of patients, The current study aimed to identify virulence and antibiotic resistance factors of the predominant bacteria associated with prostate cancer and urinary tract infection. Isolates were collected from urine samples of prostate cancer and urinary tract infection patients from Imam Hassan Al-Mujtaba Hospital and Imam Zain Al-Abidin Hospital Hospital. These specimens were cultured on conventional and specific agars and were confirmed by morphological and biochemical tests and the automated method (VITEK®2). Antimicrobial susceptibility testing was performed on the isolates by the disk diffusion method.Multiplex PCR was used to assess the presence of eight virulence genes fimH, hly, papC, cnf1, int A, aer. and resistance genes include the bla-TEMand qnrgenes. RSULTS:The most frequent bacteria linked to prostate cancer that causes UTIs is Escherichia coli. Among bacteria recovered from individuals with prostate cancer, IntA was the most prevalent virulence factor (54.5%), followed by pap C (45.4%), fimH(36.3%), cnf1 (36.3%), hly (36.3%), and aer (27.2%). whereas bla-TEM (45.4%) and qnr (54.5%) were the most common resistance genes. Cnf1 (63.6%), fimH, hly, and int A (54.5%) were the most common virulence factors in UTI patients, but papC and aer produced (45.4%), qnr, and bla-TEM (63.6%) were also common.